Lack of association between SIX1/SIX6 locus polymorphisms and pseudoexfoliation syndrome in a population from the Republic of Korea. Issue 52 (30th December 2022) - Lee, Young Chun; Lee, Mee Yon; Shin, Hye-Young
Abstract : Previous studies have reported the association of the SIX1/SIX6 locus with open-angle glaucoma in various ethnic populations. However, the relevance of the SIX1/SIX6 locus to pseudoexfoliation syndrome (XFS) appears uncertain at present. Thus, we investigated the relationship between polymorphisms in the SIX1/SIX6 locus and XFS in a Korean XFS cohort. A total of 246 participants comprising 167 unrelated Korean patients with XFS and 79 ethnically matched control subjects were recruited. Four polymorphisms of the SIX1/SIX6 locus (rs33912345, rs12436579, rs2179970, and rs10483727) were genotyped using a TaqMan® allelic discrimination assay. Genotypic and allelic associations were analyzed using logistic regression. The minor allele frequency (MAF) of rs33912345 was found to be 0.287 and 0.247 in the XFS cases and controls, respectively, and the MAF of rs12436579 was found to be 0.383 and 0.361 in the XFS cases and control subjects, respectively. The MAF of rs2179970 was found to be 0.090 and 0.095 in the XFS cases and control subjects, respectively, and the MAF of rs10483727 was found to be 0.293 and 0.253 in the XFS cases and control subjects, respectively. Genetic association analysis of 4 SIX1/SIX6 locus single nucleotide polymorphisms (SNPs) revealed no significant difference in genotype distribution between the XFS cases and control subjects in the allelic, dominant, or recessive models (all, P > .05). The current study suggested that SIX1/SIX6 locus polymorphisms (rs33912345, rs12436579, rs2179970, and rs10483727) may not be associated with a genetic susceptibility to XFS in a Korean cohort.